Effect of Sildenafil in Neonates with Persistent Pulmonary Hypertension: An Interventional Study - Jigar Jain; Jolly Vaishnav; Arif Vohra; Mansi Shah; Anika Goyal (JCDR Research and Publications Pvt. Ltd., 2024)
Introduction: Persistent Pulmonary Hypertension of the Newborn (PPHN) reflects a disruption of the normal perinatal circulatory transition and is characterised by high pulmonary artery pressure. Inhaled Nitric Oxide (iNO) is considered the mainstay of treatment for PPHN. However, many developing and resource limited countries do not have access to such expensive therapy. Therefore, sildenafil, due to its easy availability and low cost, becomes the most commonly used drug in the management of PPHN in such settings. Aim: To study the treatment response and outcomes of neonates who received sildenafil for the management of PPHN. Materials and Methods: The present hospital-based prospective interventional study was conducted in the Neonatal Intensive Care Unit (NICU), BJ Medical College, Civil Hospital, Ahmedabad, Gujarat, between May 1, 2020, and April 30, 2021. Study was conducted on neonates with meconium aspiration syndrome and/or severe birth asphyxia admitted to the NICU. A total of 48 neonates with Two Dimensional (2D) echocardiography-proven PPHN were enrolled. Baseline clinical parameters including heart rate, respiratory rate, preductal and postductal Saturation of Peripheral Oxygen (SpO2), Oxygenation Index (OI), Saturation Oxygen Distending Pressure Index (SOPI), and Non Invasive Blood Pressure (NIBP) were monitored every six hours. Neonates who were on invasive/non invasive ventilation had their Fraction of Inspired Oxygen (FiO2), Positive End Expiratory Pressure (PEEP), Peak Inspiratory Pressure (PIP), respiratory rate and flow rate monitored every six hours. Data were statistically analysed using Analysis of Variance (ANOVA) test. Results: During the study period, a total of 1080 neonates were admitted with meconium aspiration syndrome and/or severe birth asphyxia, out of which 48 neonates showed findings suggestive of PPHN on 2D echocardiography. A statistically significant improvement in oxygenation after sildenafil treatment was indicated by a significant reduction in OI from 35.3±8.6 to 13.2±2.1 (p-value <0.001), a reduction in SOPI from 3.6±0.3 to 1.5±0.2 (p-value <0.001), a reduction in FiO2 (%) from 94.6±8.19 to 24.2±4.5 (p-value <0.001), an increase in Partial pressure of oxygen (PaO2) (mmHg) from 52±5.6 to 72±3.4 (p-value <0.001), and an increase in SpO2 (%) from 83.5±8.6 to 93.5±5.1 (p-value <0.001). Conclusion: The findings of the present study suggest that oral sildenafil can be successfully used to improve oxygenation in patients with PPHN, especially in a resource limited setting where facilities like Extracorporeal Membrane Oxygenation (ECMO) and iNO are not available, as demonstrated in the present study.